2023
DOI: 10.1002/micr.31081
|View full text |Cite
|
Sign up to set email alerts
|

Supermicrosurgery with perforator‐to‐perforator anastomoses for lower limb reconstructions – A systematic review and meta‐analysis

Abstract: BackgroundSupermicrosurgical flaps based on perforator‐to‐perforator microanastomoses have been described for lower limb reconstruction. This approach offers the benefit of raising short pedicles while sparing axial vessels, which effectively enables complex reconstructive techniques in comorbid patients at high risk of reconstructive failure. The aim of our study is to assess the surgical outcomes of perforator‐to‐perforator based flaps in comparison to conventional free flaps for reconstructions of the lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…In a recent meta-analysis, Lo Torto et al found just 1047 reported cases of perforator-to-perforator flaps in the scientific literature. 27 The pooled flap failure rate reported was 6.8%. The six perforator-to-perforator flaps in our study cohort neither required revision nor suffered from complications.…”
Section: Discussionmentioning
confidence: 97%
“…In a recent meta-analysis, Lo Torto et al found just 1047 reported cases of perforator-to-perforator flaps in the scientific literature. 27 The pooled flap failure rate reported was 6.8%. The six perforator-to-perforator flaps in our study cohort neither required revision nor suffered from complications.…”
Section: Discussionmentioning
confidence: 97%